Reducing consecutive collisions in sensing based semi persistent scheduling for cellular-V2X - Jung, So Yi; Cheon, Hye Rim; Kim, Jae Hyun (IEEE Vehicular Technology Conference, 2019)
Cellular-vehicle to everything (Cellular-V2X) has been designed to support Long Term Evolution (LTE) communication standard, whereas direct short range communication (DSRC) is based on IEEE 802.11p. In this paper, we focus on cellular-V2X with Mode 4, where vehicles schedule their resources in a distributed way employing sensing based semi persistent scheduling (SPS) to avoid collision of cooperative awareness message (CAM). We analyze the effect of Mode 4 configuration and some parameters on the performance. We find that reselection counter is one of the key parameters that has an effect on consecutive collisions. Therefore, we propose a resource alternative selection (RAS) algorithm based on SPS, which reserves and allocates the multi-resources alternatively during the period of reselection counter. The simulation results show that the proposed RAS algorithm can significantly improve performance, which can not only increase message reception reliability (MRR) but also decrease consecutive message collisions.
Keywords: Cellular-V2X; Distributed scheduling; LTE-V2X; Mode 4; Resource management; Resource-scheduling; Sensing based semi persistent scheduling (SPS); Sidelink; Cellular-V2X; Distributed scheduling; LTE-V2X; Mode 4; PC5; Resource management; Resource scheduling; Sensing based semi persistent scheduling (SPS); Sidelink; V2X